Twelve-Week Quadriceps Strength as A Predictor of Quadriceps Strength At Time Of Return To Sport Testing Following Bone-Patellar Tendon-Bone Autograft Anterior Cruciate Ligament Reconstruction - Hannon, Joseph P (Int J Sports Phys Ther, 2021)
BACKGROUND: Restoration of quadriceps strength following anterior cruciate ligament reconstruction (ACL-R) continues to challenge both patients and clinicians. Failure to adequately restore quadriceps strength has been linked to decreased patients’ self-reported outcomes and an increased risk for re-injury. Early identification of quadriceps strength deficits may assist in tailoring early interventions to better address impairments. PURPOSE: The purpose of this study was to assess the relationship between early (12 weeks following ACL-R) isokinetic peak torque and isokinetic peak torque at time of return to sport (RTS) testing. STUDY DESIGN: Cohort Study METHODS: A total of 120 participants (males = 55; females =65) were enrolled in the study (age = 16.1±1.4 yrs; height = 1.72±10.5 m; mass = 70.7±16.3 kg). All participants were level 1 or 2 cutting and pivoting sport athletes who underwent a primary bone-patellar tendon-bone autograft ACL-R. Participants were tested at two time points: 12 weeks following surgery and again at time of RTS testing. A linear regression model was carried out to investigate the relationship between age, sex, and isokinetic peak torque at 12 weeks following ACL-R and isokinetic peak torque at time of RTS testing. RESULTS: When 12-week isokinetic peak torque was entered first for the hierarchy regression analysis, this factor was predictive of the peak torque at the time of RTS testing, F(1, 118) = 105.6, p < 0.001, R(2) = 0.472, indicating that the 12-week quadriceps strength accounted for 47% of the variance in the quadriceps strength at the time of RTS testing. When age and sex were added in the regression analysis, both factors only added 0.8% of variance for the quadriceps strength at the time of RTS testing. CONCLUSION: Isokinetic peak torque at 12 weeks following surgery was shown to be a significantly strong predictor (47%) for isokinetic quadriceps strength recovery at time of RTS. This finding underscores the importance of early restoration of quadriceps strength and that while non-modifiable factors such as sex and age are important, early restoration of quadriceps strength most strongly influences late stage quadriceps strength. LEVEL OF EVIDENCE: 3